Model Pelatihan dan Pengembangan Karyawan PT Parador Management International - Komeliantari, Aprinda (Jurnal Utilitas, 2016)
The study aims to know employee training and development model at PT Parador Management International and utilized descriptive qualitative model by observing employee training and development model according to Schuler dan Jackson. The data collection technique used is observation, interview and document analysis. The data analysis technique used is interactive model according to Miles and Huberman, comprises of three things: data reduction, data display and conclusion. There are three dimensions of employee training and development. The first dimension is the stage of assessment, the indicators are need assessment and goal achievement. The second dimension is the stage of training and development, the indicators are media selection and learning principle, facilitating training, and creating condusive condition. The third dimension is the stage of evaluation, the indicators are performance development, pre-test, training monitoring, training evaluation, and transfer evaluation. Based on analysis result, it was concluded the employee training and development model has been running well according to the model of Schuler and Jackson. The company need to maintain the well-run dimensions but on the third dimension, the stage of evaluation, especially in the indicator of pre-test, the company need to do pre-test to see the effectiveness of training and development, it is not enough done by only asking the participant on the beginning of training.